Odpowiedzi

2009-12-02T20:32:59+01:00
A) 1 / √14 + √21 + √15 + √10
√14/14+√21+√15+√10= √14/14 + 14√21/14 + 14√15/14 + 14√10/14=
(√14+14√21 + 14√15 +14√10)/14

b) 1 / √6 + √3 - √10 - √5
√6/6+ 6√3/6 -6√10/6 - 6√5/6=
(√6+ 6√3 - 6√10 -6√5) / 6


c) 3 / 1 + √2 - √3 = 3+ √2-√3
2009-12-02T20:34:07+01:00
A) 1*(√14 -√21-√15-√10)/ √14+√21+√15+√10 * √14 -√21-√15-√10= -√32/14-21-15-10= -√32/-32

b)1*(√6-√3+√10+√5) / √6+√3-√10-√5 * √6-√3+√10+√5= √18/-6

c) 3*(1-√2+√3)/ 1+√2+√3 * 1-√2+√3 = 3- 3√2+3√3/ 6= √2+√3/2